Associations of prenatal methylmercury exposure and maternal polyunsaturated fatty acid status with neurodevelopmental outcomes at 7 years of age: results from the Seychelles Child Development Study Nutrition Cohort 2. Issue 2 (17th December 2020) - Strain, J J; Love, Tanzy M; Yeates, Alison J; Weller, Daniel; Mulhern, Maria S; McSorley, Emeir M; Thurston, Sally W; Watson, Gene E; Mruzek, Daniel; Broberg, Karin; Rand, Matthew D; Henderson, Juliette; et al.
ABSTRACT: Background: Fish is a primary source of protein and n-3 PUFA but also contains methylmercury (MeHg), a naturally occurring neurotoxicant to which, at sufficient exposure levels, the developing fetal brain is particularly sensitive. Objectives: To examine the association between prenatal MeHg and maternal status of n-3 and n-6 PUFA with neurodevelopment, and to determine whether PUFA might modify prenatal MeHg associations with neurodevelopment. Methods: We examined the Seychelles Child Development Study Nutrition Cohort 2 (NC2) at age 7 y. We used a sophisticated and extensive neurodevelopmental test battery that addressed 17 specific outcomes in multiple neurodevelopmental domains: cognition, executive and psychomotor function, language development, behavior, scholastic achievement, and social communication. Analyses were undertaken on 1237 mother-child pairs with complete covariate data (after exclusions) and a measure of at least 1 outcome. We examined the main and interactive associations of prenatal MeHg exposure (measured as maternal hair mercury) and prenatal PUFA status (measured in maternal serum at 28 weeks' gestation) on child neurodevelopmental outcomes using linear regression models. We applied the Bonferroni correction to account for multiple comparisons and considered P values <0.0029 to be statistically significant. Results: Prenatal MeHg exposure and maternal DHA and arachidonic acid (20:4n-6) (AA) status were not significantly associated with any neurodevelopmental outcomes. Findings for 4 outcomes encompassing executive function, cognition, and linguistic skills suggested better performance with an increasing maternal n-6:n-3 PUFA ratio ( P values ranging from 0.004 to 0.05), but none of these associations were significant after adjusting for multiple comparisons. No significant interaction between MeHg exposure and PUFA status was present. Conclusions: Our findings do not support an association between prenatal MeHg exposure or maternal DHA and AA status with neurodevelopmental outcomes at age 7 y. The roles of n-6 and n-3 PUFA in child neurodevelopment need further research.